The idea of modern Jewish culture - Schweid, Eliezer, 1929-2022.; Hadari, Amnon; Levin, Leonard, 1946- (Boston : Academic Studies Press, 2008)
The vast majority of intellectual, religious, and national developments in modern Judaism revolve around the central idea of "Jewish culture." This book is the first synoptic view of these developments that organizes and relates them from this vantage point. The first Jewish modernization movements perceived culture as the defining trait of the outside alien social environment to which Jewry had to adapt. To be "cultured" was to be modern-European, as opposed to medieval-ghetto-Jewish. In short order, however, the Jewish religious legacy was redefined retrospectively as a historical "culture," with fateful consequences for the conception of Judaism as a humanly- and not only divinely-mandated regime. The conception of Judaism-as-culture took two main forms: an integrative, vernacular Jewish culture that developed in tandem with the integration of Jews into the various nations of western-central Europe and America, and a national Hebrew culture which, though open to the inputs of modern European society, sought to develop a revitalized Jewish national identity that ultimately found expression in the revival of the Jewish homeland and the State of Israel.
Culture as a concept and culture as an ideal -- Tensions and contradiction -- Internalizing the cultural ideal -- The underlying philosophy of Jewish enlightenment -- The meaning of being a Jewish-Hebrew maskil -- Crossroads: the transition from haskalah to the science of Judaism -- The dialectic between national Hebrew culture and Jewish idealistic humanism -- The philosophic historic formation of Jewish humanism: a modern guide to the perplexed -- The science of Judaism : research in Judaism as a culture -- The science of Judaism, Reform Judaism, and historical positivism -- A critique of the science of Judaism and the cultural ideal of the enlightenment -- Accelerated change and revolution -- The vision of Jewish cultural renaissance in political Zionism -- The pioneering (ḥalutzic) culture of the Jewish labor movement in Palestine -- Polar views on sources of Jewish culture -- Alienation from religion and tradition -- The Jewish folk culture of Eretz Israel -- Judaism as the totality of a national historic culture -- Sanctity and the Jewish national movement -- The dimension of sanctity in pioneering Labor Zionism -- Orthodox Zionist culture: sanctifying modernity -- Judaism as a culture in the diaspora -- The secular Jewish culture of Yiddish -- The transition from the Hebrew culture of pre-state Eretz Israel to Israeli culture.
Includes bibliographical references (pages 263-268) and index.
In English.
eBooks on EBSCOhost
Keywords: Judaism -- History -- Modern period, 1750-; Jews -- Intellectual life; Jews -- Identity; Judaism -- 20th century; Zionism -- Philosophy; Juifs -- Vie intellectuelle; Juifs -- Identité.; Judaïsme -- Histoire -- 20e siècle.; RELIGION -- Judaism -- History; Jews -- Identity; Jews -- Intellectual life; Judaism; Judaism -- Modern period; Zionism -- Philosophy; Since 1750; History